Improving pH buffering capacity of an acid soil to regulate nutrient retention and mitigate water pollution using Calciprill and sodium silicate - Ng, Ji Feng; Ahmed, Osumanu Haruna; Omar, Latifah; Jalloh, Mohamadu Boyie; Kwan, Yee Min; Musah, Adiza Alhassan; Chowdhury, Ahmed Jalal Khan (Elsevier, 2024)
In the tropics, high rainfalls and hot temperatures cause the formation of highly weathered acid soils with low pH buffering capacity (pHBC). Such soils are prone to nutrient losses via leaching, surface runoff, and volatilization. The poor nutrient retention of the highly weathered soils can cause environmental pollution in water bodies and detrimentally affect aquatic ecosystem. A preliminary study was conducted by mixing an acid soil (Bekenu series, Typic Paleudults) with Calciprill (80 %, 90 %, and 100 % Ca saturation) and sodium silicate (90, 105, 120, 135, and 150 kg ha−1) to determine the effects of the amendments on pH and pHBC of Bekenu series. Furthermore, a soil incubation study was carried out to determine the relationship between pH, pHBC, and effective cation exchange capacity (ECEC) after the soil was applied with Calciprill and sodium silicate and incubated for 40, 80, and 120 days. After the soil was harvested, the relationship between pHBC with soil exchangeable ammonium (NH4 +), available nitrate (NO3 -), and available phosphorus (P) to determine whether the combined use of Calciprill and sodium silicate is able to mitigate N and P losses through surface runoff and leaching to contaminate the surface and underground water bodies. The results from the studies showed that Calciprill and sodium silicate significantly increased soil pH and pHBC of Bekenu series. Notably, in the soil incubation study, the treatments with Calciprill and sodium silicate consistently improved pHBC compared with the soil without these amendments, suggesting that C2S4 (Calciprill at 90 % Ca saturation and sodium silicate at 135 kg ha−1) is the minimum amount of the amendments required to improve the pHBC of Bekenu series. The significant positive correlation between pH, pHBC, and ECEC throughout the soil incubation study indicates that the amendments are capable of improving pHBC of the Bekenu series when the pH and ECEC increase because of their alkalinity in addition to the presence of carbonate and silicate minerals. The significant positive correlations between pHBC with exchangeable NH4 + and available P at 40 and 80 DAI suggest that the Calciprill and sodium silicate can improve NH4 + and P availability for crop uptake. On the contrary, the significant negative correlation between pHBC and available NO3 - at 80 DAI also suggests that the combined use of amendments can significantly reduce the NO3 - contamination in water bodies because of improved pHBC. The most suitable combination for improving soil pH, ECEC, and pHBC is C2S4 (Calciprill at 90 % Ca saturation and sodium silicate at 135 kg ha−1) and it is possible to co-apply Calciprill and sodium silicate to mitigate NO3 - contamination in water bodies. To further validate the findings of this study, greenhouse study is recommended to elucidate the plant-soil interactions.